The eagle: a model for policy analysis of macroeconomic interdependence in the euro area - Gomes, Sandra; Jacquinot, Pascal; Pisani, Massimiliano (Frankfurt am Main, 2010)
"Building on the New Area Wide Model, we develop a 4-region macroeconomic model of the euro area and the world economy. The model (EAGLE, Euro Area and Global Economy model) is microfounded and designed for conducting quantitative policy analysis of macroeconomic interdependence across regions belonging to the euro area and between euro area regions and the world economy. Simulation analysis shows the transmission mechanism of region-specific or common shocks, originating in the euro area and abroad."